AB0146 Rebamipide Inhibits IL-1β-Induced Proliferation of rheumatoid Arthritis Synovial Fibroblasts Through the Phosphor-Jun N-Terminal Kinase (P-JNK) Pathway. (9th June 2015) - Lee, W.S.; Choi, Y.J.; Cheon, Y.-H.; Hong, M.-J.; Lee, C.-H.; Lee, M.S.; Lee, S.-I.; Yoo, W.-H.
Abstract : Background: Rebamipide is an antiulcer drug that protects gastric epithelial cells, improves gastric defense mechanisms by increasing gastric mucus, increases prostaglandin production, and reduces free oxygen radicals. Interestingly, recent research has demonstrated that rebamipide acts as an oxygen radical scavenger and also exhibits anti-inflammatory activity. Objectives: We determined the effects of rebamipide on the production of proinflammatory mediators, including MMPs, COX-2, and PGE2, and signaling pathway produced by rheumatoid arthritis synovial fibroblasts (RASFs) and the proliferation of these cells after stimulation with IL-1β. Methods: The proliferation of RASFs was evaluated with CCK-8 reagent in the presence of IL-1β with/without rebamipide. The expression of MMPs, tissue inhibitor of metalloproteinase-1 (TIMP-1), COXs, members of the intracellular mitogen-activated protein kinase (MAPK) signaling pathway, including p-ERK, p-p38, p-JNK, and nuclear factor-kappaB (NF-κB), and the production of PGE2 were examined by western blotting or semi-quantitative RT-PCR and ELISA. Results: Rebamipide inhibited IL-1β–induced RASF proliferation. The inhibitory effects of rebamipide were significantly enhanced in a dose-dependent manner. IL-1β enhanced the expression of MMP-1 and MMP-3, but not that of TIMP-1, in RASFs, as per the results of mRNA expression. The expression of MMP-1 and MMP-3 were significantly inhibited by treatment with rebamipide at 48 h. IL-1β phosphorylated the intracellular NK-κB and MAPKs including ERK, p-38, and JNK. Rebamipide significantly inhibited IL-1β–induced NF-κB and intracellular JNK activation, but it did not inhibit the activation of ERK and p-38. Conclusions: To the best of our knowledge, this is the first study to report that repamipide can inhibit the IL-1β-induced proliferation of RASFs via the inhibition of IL-1β-induced activation of NF-κB and phosphorylation of the JNK pathway. These findings suggest that rebamipide may be beneficial for the treatment of patients with RA. Disclosure of Interest: None declared